Despotic Leadership, Emotional Exhaustion, And Employee Sabotage: The Moderating Role of Employee Resilience - Ghulam Qamar; Dr Mubashar Hassan Zia (International Journal of Business and Economic Affairs, 2025)
In contemporary organizational environments, leadership behaviors play a decisive role in shaping employee attitudes and behaviors. Among destructive leadership styles, despotic leadership has emerged as particularly harmful due to its authoritarian, self-serving, and exploitative nature. This study investigates the moderating role of employee resilience as well as the indirect impact of despotic leadership on employee sabotage through emotional exhaustion, drawing on the theories of Conservation of Resources (COR) and Social Exchange (SET). Data were gathered from workers in the FMCG industry using a quantitative, cross-sectional survey design. The findings reveal that despotic leadership significantly increases emotional exhaustion, which in turn fosters sabotage behaviors. Additionally, employee resilience reduces the positive correlation between sabotage and emotional exhaustion, demonstrating its protective effect against negative workplace consequences. By emphasizing emotional exhaustion as a crucial mechanism connecting despotic leadership to sabotage and identifying resilience as an essential personal resource that lessens these negative effects, this study adds to the literature on leadership and organizational behavior.